2012
DOI: 10.1111/j.1750-3639.2012.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Truncated α‐Synuclein and Aggregates in Parkinson's Disease and Incidental Lewy Body Disease

Abstract: The role of Lewy bodies, Lewy neurites and α-synuclein (αSYN) in the pathophysiology and diagnosis of Parkinson’s disease (PD) is unclear. We used postmortem human tissue, a panel of antibodies (Abs) and confocal microscopy to examine the three-dimensional neurochemical anatomy of the nigrostriatal system. Abs were specific to truncated (tαSYN), phosphorylated and full-length αSYN. The findings demonstrate the critical role of tαSYN in initiating aggregation, a role for other forms of αSYN in aggregate expansi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
67
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 57 publications
15
67
0
Order By: Relevance
“…Treatment of microglia with tAS leads to a significant increase of ROS production and release of IL-6, CXCL1, and TNF-α. Our results suggest that tAS which was reported previously as a component of Lewy bodies and glial cytoplasmic inclusions (Baba et al,1998; Gai et al,1999; Prasad et al,2012) may play an important pathogenic role to accelerate neuroinflammation and oxidative stress in ASP. Microglia treated with sAS and fAS also present an augmented ROS production and phagocytic activity.…”
Section: Discussionsupporting
confidence: 70%
“…Treatment of microglia with tAS leads to a significant increase of ROS production and release of IL-6, CXCL1, and TNF-α. Our results suggest that tAS which was reported previously as a component of Lewy bodies and glial cytoplasmic inclusions (Baba et al,1998; Gai et al,1999; Prasad et al,2012) may play an important pathogenic role to accelerate neuroinflammation and oxidative stress in ASP. Microglia treated with sAS and fAS also present an augmented ROS production and phagocytic activity.…”
Section: Discussionsupporting
confidence: 70%
“…To exclude the possibility that the variations in the synapsin-III levels observed in primary neurons were due to non-dopaminergic neurons or glial cells present in the primary cell cultures, we evaluated the expression of synapsin III in a more uniform dopaminergic cell population -dopaminergic differentiated SH-SY5Y neuroblastoma cells (Bellucci et al, 2008) To confirm whether α-syn affected DAT and synapsin III distribution, besides their expression, we used a differentiated neuronal SK-N-SH cell line that stably expressed a green fluorescent protein (GFP)-conjugated form of DAT to overexpress the SYN120 mutant protein (Bellucci et al, 2011a). This form of α-syn can be found in LBs (Prasad et al, 2012), and promotes α-syn aggregation (Crowther et al, 1998), DAT redistribution (Bellucci et al, 2011a) and the induction of axonal and synaptic damage (Games et al, 2013;GarciaReitbock et al, 2010). We found that SYN120-expressing cells showed intracellular α-syn-and synapsin-III-immunopositive inclusions that contained DAT-GFP, whereas, in control SK-N- SH DAT-GFP cells, both synapsin III and DAT localized predominantly at the plasma membrane (supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Various engineered recombinant truncated forms of aSyn aggregate readily in vitro and form toxic inclusions when overexpressed in animal models (14)(15)(16)(17). Furthermore, C-terminally truncated aSyn is ubiquitously present in Lewy bodies of PD brains, and the amount of truncated forms is correlated with the number and size of Lewy bodies (18,19), suggesting that truncation of aSyn might be an early event that renders it more prone to aggregate into disease-associated conformations. A number of in vitro studies have investigated this possibility and have implicated different proteases that theoretically could truncate aSyn, including neurosin (20), 20S proteasome (21,22), calpain-1 (23), matrix metallo-proteases (MMPs) (24), and cathepsin D (25).…”
Section: Significancementioning
confidence: 99%